Differentiated Use Of Antidepressants In The Recovery Therapy System Of Psycho-Social Rehabilitation Of Patients With Depressive Disorders - Mykhaylov, Borys; Jivilova, Jana (Psychiatry, Neurology and Medical Psychology)
Currently depressive disorders occupy a leading place in the structure of morbidity in the world. So far, the actual problem is the choice of therapeutic tactics in the treatment of depressive states of various origins. A characteristic feature of modern clinical depression, including the one in Ukraine, is the prevalence of complaints of psychosensory and somatovegetative nature. It dictates certain requirements for the choice of antidepressants with regard to their possible side effects. Currently the basic mechanisms of action of antidepressants based on synaptic transmission process are being outlined. In pharmacotherapy of depressive disorders, including organic origin, possible side effects of antidepressants must be taken into account. It is important to maintain compliance relationships with patients, to prevent self-discontinuation, improve psycho-social rehabilitation and purposeful correction of side effects taking into account the major neurochemical links.